Penguatan Literasi Keuangan Digital di Era Fintech untuk Meningkatkan Kecakapan Finansial Siswa SMA TRIGUNA 1956 Jakarta - Faridz Harfiore Akbar; Khalisha Zahra Zhafirah; Davina Viskayana Rahardjo Margo; Yeni Septiani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Abstract. The development of financial technology (fintech) has brought significant changes to the way people manage their finances. Various digital financial services, such as e-wallets, online loans, digital investments, and cashless payment systems, are now increasingly accessible to the wider public. However, this convenience has not been fully matched by an adequate level of digital financial literacy, potentially giving rise to various risks in their use. This Community Service (PKM) activity aims to improve the understanding, awareness, and skills of Triguna 1956 Jakarta Senior High School students in utilizing digital financial services wisely, safely, and responsibly. The activity implementation methods included outreach, interactive training, discussions, and evaluation of participants' understanding. The results of the activity showed an increase in participants' knowledge of the basic concepts of fintech, their understanding of the benefits and risks of digital finance, and their ability to implement safe financial management practices in the digital era. This activity is expected to support the strengthening of digital financial literacy and inclusion, especially in secondary education settings, on an ongoing basis.